The Construction of Salary Performance Management System based on the Concept of "Relative Competitiveness" - Wang, Xiaoqiong (Journal of Theory and Practice of Social Science, 2023)
In the background of the rapid development of Chinese social economy, the scope of enterprise human resource management is gradually expanding and the content is increasing, which directly affects whether the enterprise strategic goals can be realized. At the present stage, enterprises often encounter some problems in the compensation and performance management in the process of development, which leads to the unreasonable compensation of employees and reduces their enthusiasm for work. In the face of this situation, enterprises need to build a salary and performance management system under the concept of "relative competitiveness", so as to ensure that employees' remuneration is reasonable and inject impetus into the development of enterprises.